Computed Tomography of the Coronary Arteries - de Feyter, P.J.; Weustink, A.; Alberghina, F.; Gruszczynska, K.; van Pelt, N.; Pugliese, F.; Mollet, N. (SA Heart Journal, 2017)
MSCT Coronary Angiography is a fast developing non-invasive diagnostic technique that can detect a coronary stenosis. The detection of a coronary stenosis is hampered by limited image quality and by motion artefacts and extensive calcifications. However, MSCT-coronary angiography is highly reliable to rule out coronary stenosis. The role of MSCT-coronary angiography in the diagnostic work-up of coronary artery disease needs further research.